Taḥlīlu Istiqbāli al Adabi Naḥwa Riwāyatin; Imra’atun ‘Inda Nuqṭati al Ṣifri li Nawāli al Sa’dāwi (Dirāsatun Taḥlīliyyatun fī Manẓuri al Adabi) - Rahmadini, Ayu; Yusuf, Muhammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
This study aims to describe the intrinsic elements consisting of Themes, Characters and Characterizations, Setting, Plot, and Language in the novel Imra'ah 'Inda Nuqthah As-Shifr by Nawal As-Sa'dawi through the reader's reception and to find out the criticisms and their values ​​in the novel. This research is a qualitative descriptive study using a content analysis approach. The research target is limited to 15 students of Arabic Language and Literature at the State Islamic University of Sulthan Thaha Saifuddin Jambi for the 2020/2021 Academic Year. The results of this study are as follows: Analysis of the intrinsic elements through the reader's responses there is a theme in this novel is gender injustice. The plot contained in the novel is the Backward plot because the story that is told is an incident in the past. There is one main character and ten side characters. The setting of the place in the story is in the prison of Qonathir and Egypt. The language used in this novel is a language that is quite difficult for readers to understand. This intrinsic element analysis also includes responses to the novel as well as the values ​​contained in the novel, both moral values ​​and educational values